Risk Factors for Community Acquired Extended-Spectrum Β-lactamase (ESBL) Producing Enterobacteriaceae Urinary Tract Infections (UTIs). (4th October 2017) - Goyal, Dheeraj; Dascomb, Kristin; Jones, Peter S; Lopansri, Bert K
Abstract: Background: Community-acquired extended-spectrum β-lactamase (ESBL) producing Enterobacteriaceae infections pose unique treatment challenges. Identifying risk factors associated with ESBL Enterobacteriaceae infections outside of prior colonization is important for empiric management in an era of antimicrobial stewardship. Methods: We randomly selected 251 adult inpatients admitted to an Intermountain healthcare facility in Utah with an ESBL Enterobacteriaceae urinary tract infection (UTI) between January 1, 2001 and January 1, 2016. 1:1 matched controls had UTI at admission with Enterobacteriaceae but did not produce ESBL. UTI at admission was defined as urine culture positive for > 100, 000 colony forming units per milliliter (cfu/mL) of Enterobacteriaceae and positive symptoms within 7 days prior or 2 days after admission. Repeated UTI was defined as more than 3 episodes of UTI within 12 months preceding index hospitalization. Cases with prior history of ESBL Enterobacteriaceae UTIs or another hospitalization three months preceding the index admission were excluded. Univariate and multiple logistic regression techniques were used to identify the risk factors associated with first episode of ESBL Enterobacteriaceae UTI at the time of hospitalization. Results: In univariate analysis, history of repeated UTIs, neurogenic bladder, presence of a urinary catheter at time of admission, and prior exposure to outpatient antibiotics within past one month were found to be significantly associated with ESBL Enterobacteriaceae UTIs. When controlling for age differences, severity of illness and co-morbid conditions, history of repeated UTIs (adjusted odds ratio (AOR) 6.76, 95% confidence interval (CI) 3.60–13.41), presence of a urinary catheter at admission (AOR 2.75, 95% CI 1.25 – 6.24) and prior antibiotic exposure (AOR: 8.50, 95% CI: 3.09 – 30.13) remained significantly associated with development of new ESBL Enterobacteriaceae UTIs. Conclusion: Patients in the community with urinary catheters, history of recurrent UTIs, or recent antimicrobial use can develop de novo ESBL Enterobacteriaceae UTIs. Disclosures: All authors: No reported disclosures.